2008
DOI: 10.1159/000176300
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden among Caregivers of Koreans with Dementia

Abstract: Background: Most studies on caregiver burden have been conducted in Western countries, while few studies on the correlates of caregiver burden have been performed in Korea. Objective: To suggest better policies for the care of dementia patients by using a nationwide database to identify factors that affect caregiver burden in Korea. Methods: The database of the Korean National Health Insurance (KNHI) and National Medical Aid (NMA) programs, which covers all Koreans, was used. A sample of 609 dementia patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 66 publications
5
52
1
5
Order By: Relevance
“…Other studies have reported an inverse relationship between income and level of strain, i.e., caregivers with low income or high financial strain exhibited higher burden [2,45]. It is difficult to compare our results with these studies due to methodological differences.…”
Section: A Slachevsky Et Al / Burden In Caregivers Of Patients Withmentioning
confidence: 55%
See 1 more Smart Citation
“…Other studies have reported an inverse relationship between income and level of strain, i.e., caregivers with low income or high financial strain exhibited higher burden [2,45]. It is difficult to compare our results with these studies due to methodological differences.…”
Section: A Slachevsky Et Al / Burden In Caregivers Of Patients Withmentioning
confidence: 55%
“…The evidence on the relationship between caregiver burden and functional status has been inconsistent. Some studies have found that functional status is associated with caregiver burden [45,46] but others have not [27]. Cognition [40], or cognitive-functional status, has been found to be a predictor of caregiver burden, but explained less variance than behavioral disturbances [33].…”
Section: A Slachevsky Et Al / Burden In Caregivers Of Patients Withmentioning
confidence: 99%
“…Mohamed et al3 found that severity of psychiatric symptoms, behavioral disturbances, and patient quality of life have a stronger association with caregiver-experienced burden. Kim et al5 reported that caregiver-related factors, such as gender, history of home care, and education level are correlated with caregiver burden. Additionally, patient-related factors such as performance of activities of daily living (ADLs) have been related to burden.…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, by contrast, the recruitment process can be more representative thanks to the availability of nationwide databases. One study (Kim, Hong, Lee, Kim, Kang, & Lee, 2008) used the two nationwide databases which cover all Koreans in South Korea (e.g., the Korean National Health Insurance and National Medical Aid). The authors recruited the sample of dementia patients and their family caregivers using random sampling by stratification according to age, sex, and region of residence .…”
Section: Summary Of Reported Resultsmentioning
confidence: 99%